Principal components selection for dimensionality reduction using discriminant information applied to fault diagnosis. (September 2015) - Prieto-Moreno, A.; Llanes-Santiago, O.; García-Moreno, E.
Abstract : Highlights: Use of the discriminant information contained on the principal components for their selection. Use of statistical hypothesis test as distance measurements between multiple classes. The concept of the classifier profile is introduced to study the classifier performance. Abstract: The Principal Component Analysis is one of most applied dimensionality reduction techniques for process monitoring and fault diagnosis in industrial process. This work proposes a procedure based on the discriminant information contained in the principal components to determine the most significant ones in fault separability. The Tennessee Eastman Process industrial benchmark is used to illustrate the effectiveness of the proposal. The use of statistical hypothesis tests as a separability measure between multiple failures is proposed for the selection of the principal components. The classifier profile concept has been introduced for comparison purposes. Results show an improvement in the classification process when compared with traditional techniques and the StepWise selection. This has resulted in a better classification for a fixed number of components, or a smaller number of required components to obtain a prefixed error rate. In addition, the computational advantage is demonstrated.